2001
DOI: 10.1046/j.1523-1755.2001.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to meat protein intake and hyperoxaluria in idiopathic calcium stone formers

Abstract: Approximately one third of ICSFs with or without so-called MMH are sensitive to meat protein in terms of oxalate excretion, as opposed to healthy subjects. Mechanisms underlying this sensitivity to meat protein remain to be elucidated and do not seem to involve vitamin B(6) deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…A high animal protein diet increases urinary calcium, uric acid, oxalate, and phosphorus and decreases urinary citrate and pH, as an effect of a higher intake of purine and phosphorus and urinary acidification [7-9]. Similar lithogenic changes have been reported with high carbohydrate and fat intake [10-12].…”
Section: Introductionmentioning
confidence: 88%
“…A high animal protein diet increases urinary calcium, uric acid, oxalate, and phosphorus and decreases urinary citrate and pH, as an effect of a higher intake of purine and phosphorus and urinary acidification [7-9]. Similar lithogenic changes have been reported with high carbohydrate and fat intake [10-12].…”
Section: Introductionmentioning
confidence: 88%
“…For comparable animal protein loads, these urinary effects are more marked in stone formers, suggesting that these subjects may have a genetic hypersensitivity to such foods. 27 The increase in uricosuria and phosphaturia is directly related to the high purine and phosphorus content of animal proteins. The increase in calciuria and decrease in citraturia and urine pH are mainly attributed to the acidifying effect of their high content in sulfurated amino acids (methionine and cysteine).…”
Section: Proteinsmentioning
confidence: 99%
“…In a study it was shown overconsumption of animal protein create observable increased rate of urinary calcium (23%) and oxalate (24%) [80]. High fructose consumption from soft drinks is associated with an increased risk of hypercalciuria, hyperoxaluria and hyperuricosuria [39,81]. In an experiment higher urinary calcium excretion occurred in rats fed high-fructose diets compared to rats fed high-starch diets [82,83].…”
Section: Calcium Stonementioning
confidence: 99%